A Practical Guide to Immunoassay Method Validation - Andreasson, Ulf; Perret-Liaudet, Armand; van Waalwijk van Doorn, Linda J. C.; Blennow, Kaj; Chiasserini, Davide; Engelborghs, Sebastiaan; Fladby, Tormod; Genc, Sermin; Kruse, Niels; Kuiperij, H. Bea; Kulic, Luka; Lewczuk, Piotr; et al. (Frontiers in Neurology, 2015)
Biochemical markers have a central position in the diagnosis and management of patients in clinical medicine, and also in clinical research and drug development, also for brain disorders such as Alzheimer’s disease. The enzyme-linked immunosorbent assay (ELISA) is frequently used for measurement of low-abundance biomarkers. However, the quality of ELISA methods varies, which may introduce both systematic and random errors. This urges the need for more rigorous control of assay performance, regardless of its use in a research setting, in clinical routine, or drug development. The aim of a method validation is to present objective evidence that a method fulfills the requirements for its intended use. Although much has been published on which parameters to investigate in a method validation, less is available on a detailed level on how to perform the corresponding experiments. To remedy this, standard operating procedures with step-by-step instructions for a number of different validation parameters is included in the present work together with a validation report template which allow for a well-ordered presentation of the results. Even though the standard operating procedures were developed with the intended use for immunochemical methods and to be used for multicenter evaluations, most of them are generic and can be used for other technologies as well.